مستقبل توازن القوى في ظل صعود قوى دولية جديدة (Comprehensive Journal of Science, 2026)
This study examines the impact of the rise of new international powers on the balance of power in the international system, reviewing the transformations witnessed in the twentieth century with the dominance of traditional powers such as the United States and the Soviet Union during the Cold War. With the beginning of the twenty-first century, the balance of power began to change with the emergence of emerging countries such as China, India, and Brazil, which significantly influenced the global political and economic system. The study provides an analysis of changes in the global economy, as emerging powers have become more influential in trade markets and economic exchanges, weakening the traditional dominance of major powers. The study also highlights the impact of these powers on the security strategies and defense policies of major countries, in addition to the reshaping of international alliances. Using a descriptive and analytical approach, the study relies on the analysis of primary and secondary data, comparing the shifts in the balance of power between major countries and emerging countries. The results indicate the increasing economic and military power of these countries, leading to new challenges in the areas of security and trade, with a greater focus on environmental issues. The rise of these powers also reshapes international politics and drives competition over economic resources in different regions of the world. The study offers recommendations to encourage cooperation between major powers. and emerging powers, emphasizing the need to promote sustainable environmental policies, reform decision-making mechanisms in international organizations, and develop the technological capabilities of emerging countries to ensure a future balance of power.
Keywords: Balance of power - International powers - International system - Rising powers